2011
DOI: 10.1039/c0cp01600d
|View full text |Cite
|
Sign up to set email alerts
|

The competitive adsorption of counter-ions at the surface of anionic surfactants solution

Abstract: We have determined the surface excess of surface active anion and counter-ions in a non-aqueous polar solution of anionic surfactants blends, as well as their distributions near the solution surface. The blends of two anionic surfactants, sodium dodecyl sulfate (SDS) and cesium dodecyl sulfate (CDS), with different contents were used as solutes to prepare the solutions. According to the isotherms that are separately fitted to the pure SDS and the pure CDS solutions (C. Wang and H. Morgner, Langmuir, 2010, 26, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Wang et al. found for the anionic surfactants sodium dodecyl sulfate (SDS) and cesium dodecyl sulfate (CDS) in formamide solutions that the surface excess depends on the alkali cation . Keeping the total surfactant concentration constant Wang et al.…”
Section: Concentration Depth Profilesmentioning
confidence: 99%
See 2 more Smart Citations
“…Wang et al. found for the anionic surfactants sodium dodecyl sulfate (SDS) and cesium dodecyl sulfate (CDS) in formamide solutions that the surface excess depends on the alkali cation . Keeping the total surfactant concentration constant Wang et al.…”
Section: Concentration Depth Profilesmentioning
confidence: 99%
“…The left panel shows the surface excess of mixed SDS/CDS formamide solution. The total surfactant concentration was kept constant and the ratio between Na + and Cs + was changed . The right panel shows the position of the cation and the anion of both the SDS and the CDS solution .…”
Section: Concentration Depth Profilesmentioning
confidence: 99%
See 1 more Smart Citation
“…80 Pluis et al 5b have investigated melting at the surface of a cylindrically shaped Pb crystal via medium-energy ion scattering. They found that open faces like (112), (113), and (115) show surface melting while the closed face (111) did not, and that surface melting is controlled by excess free energy at the surface. Surface melting was also found at the Ge(111) surface in a similar way.…”
Section: Surface Meltingmentioning
confidence: 96%
“…However, so far, only few techniques are able to directly determine the concentration-depth profiles, i.e., the distributions of the species at liquid surfaces. Those techniques incorporate neutron reflectivity (NR) [18][19][20], X-ray reflectivity (XR) [21][22][23], angular resolve X-ray photoelectron spectroscopy (ARXPS) [24][25][26][27], and neutral impact collision ion scattering spectroscopy (NICISS) [28][29][30][31][32][33]. On the other hand, recently, the computer simulation, such as Monte Carlo (MC) and molecular dynamics (MD), has been widely employed to investigate the molecular structure of liquid surfaces, for the sake of overcoming those shortcomings of and as a complement of the experimental techniques.…”
Section: Introductionmentioning
confidence: 99%